Evolution of Robotic System Specification Methodology - Figat, Maksym; Zieliński, Cezary (Wydawnictwo Politechniki Łódzkiej, 2023)
Design of robotic systems is a challenging task. More than 30 years ago some members of our team have embarked on a quest to find a general methodology for the design of any robotic system. Here we present the results that have been obtained thus far – a Robotic System Specification Methodology (RSSM). The foundation of RSSM is a metamodel – the scaffolding of any robotic system. Appropriate definition of the parameters of the metamodel transforms it into a model of a particular system, thus providing its specification, which in turn is translated into the control system code.
Keywords: robotic system specification; robotic system architecture; specyfikacja systemu robotycznego; architektura systemu robotycznego